Estafet Writing Technique in Teaching Writing Recount Text at Pesantren An-Nur Padangsidimpuan in Covid-19 Era - Seriani Hutasuhut; Eka Sustri Harida; Sri Rahmadhani (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
The main focus of the research is to find out the effect of Estafet Writing Technique on writing Recount Text at Grade XI Pesantren An-Nur Padangsidimpuan in Covid-19 era. This research was designed with quantitative research with experimental method. The sample were XI 1 as experimental class that consisted of 11 students and XI 2  as control class that consisted of 10 students. The data were collected through pre-test and post-test in essay test form and analyzed by using t-test formula. The finding showed that the mean score of experimental class was higher than the mean score of control class. After doing T-test, the researcher found that tcount ttable (6.49 2.093). Therefore, alternative hypothesis (Ha) of this research was accepted null hypothesis (H0) was rejected. It can be concluded that there was significant effect of using Estafet Writing Technique on writing Recount Text at grade XI students of MA An-Nur Padangsidimpuan in Covid-19 Era